P04.42 Utilising whole transcriptome profiling to increase understanding of mechanisms driving IDH-mutant glioma progression and recurrence. (19th September 2018) - Cho, A; Hudson, A L; Colvin, E K; Hayes, S A; Wheeler, H R; Howell, V M
Abstract: Background: Gliomas are the most common primary brain tumours in adults. IDH -mutated low-grade gliomas of astrocytic lineage (astrocytomas) have a relatively indolent clinical course; however, over time they progress to a higher grade. Molecular studies revealed recurrent tumours harbour more mutations upon malignant progression when treated with chemotherapy and/or radiotherapy compared to treatment-naïve tumours, however, genes which promote progression and recurrence in these tumours are unknown. This study aims to ascertain the natural history and treatment-induced effects of progressive IDH -mutated astrocytomas using whole transcriptome profiling. Material and Methods: This study compared differences in the whole transcriptome profiles of 6 matched pairs of primary lesions with their higher-grade recurrent lesion. Tumour specimens from three patients who presented with grade 2 lesions and received no treatment following resection were collected. Tumours from another three patients who presented with grade 3 lesions and received radiotherapy alone following surgery were also collected. The recurrent high grade tumour of each patient that was collected from the second surgery was also analysed. RNA was extracted from frozen specimens and following quality control, analysed with the Illumina Next-Generation Sequencing platform (HiSeq HT paired end, TruSeq Kit). Results: Comparison of primary and recurrent specimens identified 2042 differentially expressed genes (Fold Change ≥2) for the no-treatment group and 2066 differentially expressed genes for the radiotherapy group. Several differentially expressed gene families, including HLAs corresponding to MHC class II, cytokine families (IL, CXC, CC, TNF) and metalloproteinase families (ADAM, MMP), were associated with immune response and modification of the tumour microenvironment. The identification of these key gene families suggests the importance of the immune response and the tumour microenvironment to promote glioma progression. Conclusion: The identification of differentially expressed genes will improve our understanding of the mechanisms driving recurrence and progression of gliomas and may also reveal potential novel targets for additional therapies for this deadly cancer.